Bibliometric Analysis and Systematic Literature Review: Digital Leadership Transformation in Higher Education (2019-2025) - Arya Yusuf; Wagiran; Zainal Arifin; Ketut Ima Ismara; Sutiman; Yanuar Agung Fadlullah; Muhamad Riyan Maulana; Siti Nursipa Wulida (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the development of research on digital leadership transformation in higher education during the 2019–2025 period through a bibliometric analysis and systematic literature review (SLR). Research data were obtained from the Scopus database using the PRISMA framework, resulting in 104 documents that met the inclusion criteria. The analysis was conducted using VOSviewer software to map publication trends, collaboration networks, keywords, and dominant research themes. The results indicate that publications related to digital leadership transformation have seen a significant increase since 2023. The most productive countries in this research are the United Kingdom, the United States, Germany, and Malaysia. The most frequently appearing keywords include digital transformation, higher education, digital leadership, leadership, and sustainability. This study also identified challenges such as limited digital competencies, organizational barriers, and infrastructure readiness. However, it offers significant benefits for innovation, efficiency, and institutional resilience through strategies to strengthen competencies, foster collaboration, and integrate technology in a sustainable manner.